The Association Between Fear of Coronavirus Disease 2019, Mental Health, and Turnover Intention Among Quarantine Hotel Employees in China - Yi-Man Teng; Kun-Shan Wu; Dan Xu (Frontiers Media S.A., 2021)
During the coronavirus disease 2019 (COVID-19) pandemic, quarantine hotel employees face a higher risk of infection while they host quarantine guests from overseas. This is the first research to empirically investigate the psychological effects of operating a quarantine hotel on its employees. The empirical results indicate that heightened fear of COVID-19 leads to adverse mental health issues for quarantine hotel employees and confirm that depression, anxiety, and stress have a significant influence on turnover intention. These findings contribute to the extant knowledge base by uncovering the role of mental health in employee turnover intention. Based on the results, implications are presented for practitioners.